2014
DOI: 10.1002/ceat.201300840
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of CH4 in Hydrate in Porous Sediments with Liquid CO2 Injection

Abstract: The dynamics of the replacement of CH4 in hydrate in porous sediments with liquid CO2 was investigated using a self‐developed experimental apparatus at different temperatures and initial pressures. The pressure increases steadily as the replacement reaction processes. The amount of the replaced CH4 is almost the same as that of the CO2 forming hydrate in the early stage and gradually becomes somewhat less in the later stage. The initial pressure has minor effects on the replacement rate, and temperature reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 27 publications
0
7
0
2
Order By: Relevance
“…Presently, some exploitation techniques have been proposed and investigated for several decades. These techniques can be classified into four basic schemes: (1) depressurization, , (2) thermal stimulation, , (3) chemical stimulation, , and (4) replacement of CH 4 by carbon dioxide (CO 2 ). , Besides, some combination technologies have also been developed. Hot brine injection is the one that combines thermal stimulation with chemical stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…Presently, some exploitation techniques have been proposed and investigated for several decades. These techniques can be classified into four basic schemes: (1) depressurization, , (2) thermal stimulation, , (3) chemical stimulation, , and (4) replacement of CH 4 by carbon dioxide (CO 2 ). , Besides, some combination technologies have also been developed. Hot brine injection is the one that combines thermal stimulation with chemical stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…They defined the driving force as the gas fugacity deviation between gas and hydrate phase and treated the CH 4 escaping and the CO 2 entrapment process independently. This model was successfully applied in the replacements taken place in hydrate bearing sediments, but unable to describe the gas distributions inside the hydrate phase. , Lee et al related the shrinking core model with the Avrami equation to quantify the gas exchange in hydrate particles and proposed that gas diffusion inside the hydrate layer is considered as rate limiting step . Schicks et al complied the experimental data and noted that the conversion process should be described as a series of hydrate dissociation and reformation, which were driven by the gradient of the chemical potential between the hydrate phase and the environmental gas phase …”
Section: Introductionmentioning
confidence: 99%
“…The driving force of the CH 4 replacement in the CH 4 hydrate with liquid CO 2 was considered as the fugacity difference between the liquid and the hydrate phase. Zhang et al [344] changed the experimental conditions in the replacement reaction by use of liquid CO 2 at the different temperatures and initial pressures, and the experiment was conducted in porous sediment. His research showed that the recovery ratio of CH 4 can reach approximately 45 % after 288 h, while in Ota's experiment, [338] the recovery ratio is about 37 % after 307 h and the recovery ratio is 18.6 % after 96 h in Zhou et al's experiment.…”
Section: Experimental Simulation Via Co 2 -Ch 4 Replacementmentioning
confidence: 99%